An appearance representation for multiple reflection components - Lin, Steve; Lee, Sang W. (Computer Vision and Pattern Recognition (CVPR), 2000)
Variability in object appearance due to illumination conditions has typically been modelled for only diffuse reflection. In this paper we present a method for determining multiple reflection components for a set of photometric images, and describe a linear representation of these reflection elements for enumerating the possible illumination appearances of an object. The proposed approach involves a simultaneous estimation of reflectance parameters that can be generalized to yield a separation for an arbitrary number of reflection components. We show that the separated components of photometric images can be combined to form their counterparts in images with different illumination. Results are presented to illustrate the performance of this method for uncalibrated lighting directions.